Pola Naratif Kejatuhan Tokoh Anis dalam Naskah Sunda Carita Anis (Kajian Naratologi) - Anita Rahma Abdulah; Rohanda Rohanda; Resa Restu Pauji (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2026)
This study aims to reveal the narrative pattern of the downfall of the character Anis in Carita Anis through an analysis of its story structure. This research is qualitative in nature, employing a descriptive-analytical method through the narratological structuralism approach of Vladimir Propp. The data consist of textual excerpts depicting the narrative of a character’s decline in faith, sourced from the Carita Anis manuscript collection of the Khastara Division, National Library of the Republic of Indonesia. The analysis is conducted by mapping action functions and the distribution of character roles to examine causal relationships and the progression of the narrative. The results indicate that Carita Anis constructs a systematic and progressive scheme of narrative functions with the pattern (α), (J), (a), (B), (C), (↑), (γ), (δ), (D), (F), (K), (δ), (C), (θ), (ξ), (Ex), (U). This scheme demonstrates that the character’s loss of faith unfolds gradually, beginning with material deprivation, triggered by domestic conflict, reinforced by violations of religious prohibitions, and ultimately culminating in divine punishment. This structure underscores the function of Carita Anis as a didactic religious narrative that conveys moral and theological messages through its structural storytelling mechanism. Keywords: Carita Anis, manuscript, structure, narratology, Vladimir Propp